2024
DOI: 10.1161/circulationaha.123.066943
|View full text |Cite
|
Sign up to set email alerts
|

Stopping Aspirin Within 1 Month After Stenting for Ticagrelor Monotherapy in Acute Coronary Syndrome: The T-PASS Randomized Noninferiority Trial

Sung-Jin Hong,
Seung-Jun Lee,
Yongsung Suh
et al.

Abstract: Background: Stopping aspirin within 1 month after implantation of a drug-eluting stent (DES) for ticagrelor monotherapy has not been exclusively evaluated for patients with acute coronary syndrome (ACS). The aim of this study was to investigate whether ticagrelor monotherapy after <1 month of dual antiplatelet therapy (DAPT) is noninferior to 12 months of ticagrelor-based DAPT for adverse cardiovascular and bleeding events in patients with ACS. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The benefits of ticagrelor monotherapy were confirmed by 2 additional studies including patients with ST-segment–elevation myocardial infarction, the TICO trial ([Ticagrelor Monotherapy After 3 Months in the Patients Treated With New Generation Sirolimus Stent for Acute Coronary Syndrome]; N=3056), 20,21 and the T-PASS trial ([Ticagrelor Monotherapy in Patients Treated With New-Generation Drug-Eluting Stents for Acute Coronary Syndrome]; N=2850) 22 ; of note, these latter studies were conducted in East Asian patients only and were underpowered to detect differences in ischemic events (Table S1).…”
Section: Aspirin Discontinuationmentioning
confidence: 93%
“…The benefits of ticagrelor monotherapy were confirmed by 2 additional studies including patients with ST-segment–elevation myocardial infarction, the TICO trial ([Ticagrelor Monotherapy After 3 Months in the Patients Treated With New Generation Sirolimus Stent for Acute Coronary Syndrome]; N=3056), 20,21 and the T-PASS trial ([Ticagrelor Monotherapy in Patients Treated With New-Generation Drug-Eluting Stents for Acute Coronary Syndrome]; N=2850) 22 ; of note, these latter studies were conducted in East Asian patients only and were underpowered to detect differences in ischemic events (Table S1).…”
Section: Aspirin Discontinuationmentioning
confidence: 93%
“…The primary endpoint was a composite of adverse events including all-cause death, myocardial infarction, stent thrombosis, stroke, and major bleeding at one-year postprocedure. The trial found that short-term DAPT followed by ticagrelor monotherapy was both noninferior and superior to the longer DAPT regimen, primarily driven by a significant reduction in major bleeding events [35]. These results raise doubts about generically referring to any P2Y12i after the DAPT period, given the different pharmacokintetic profiles and efficacies in large trials (e.g., ticagrelor and clopidogrel).…”
Section: Antiplatelet Therapymentioning
confidence: 99%
“…In the T-PASS trial (Ticagrelor Monotherapy in Patients Treated With New-Generation Drug-Eluting Stents for Acute Coronary Syndrome), Hong et al 2 have further challenged the need for prolonged ticagrelor-based DAPT after PCI by studying the impact of stopping aspirin much earlier after PCI than was studied in the analyses by Baber et al Despite cessation of aspirin and subsequent use of ticagrelor monotherapy at a median of 16 days after PCI and <20% use of intravascular imaging, only 2 cases of definite or probable stent thrombosis were reported among 1426 patients in this arm, with the same number of stent thrombosis cases reported in the 1424 patients randomized to receive 12 months of ticagrelor-based DAPT. The rates of major adverse cardiac events were very low in both groups and numerically favored the arm with early aspirin cessation (1.5% versus 2.2%; P =0.17).…”
mentioning
confidence: 99%
“…As the risk of stent thrombosis recedes or if the immediate postprocedural risk is very low, the possibility emerges of alternative strategies that reduce bleeding risk without increasing stent thrombosis risk. In this issue of Circulation , 3 papers contribute further to our knowledge in the context of contemporary clinical practice, 1–3 providing further insights into possible strategies for de-escalation of antiplatelet intensity. 4,5…”
mentioning
confidence: 99%
See 1 more Smart Citation